PERBANDINGAN PENINGKATAN KADAR GULA DARAH SEBELUM DAN SETELAH PEMBERIAN GULA PUTIH, GULA AREN, DAN MADU PADA MAHASISWA TLM DI STIKes SANTA ELISABETH MEDAN TAHUN 2023 - Paska R. Situmorang; Besterria Zalukhu; David Sumanto Napitupulu (Journal of Indonesian Medical Laboratory and Science, 2023)
Glucose is the most important carbohydrate because almost all carbohydrates in food are converted to glucose for metabolism. White sugar, palm sugar and honey have different glycemic index values ??so that there is an increase in blood sugar levels with every intake of these three sugars. Several factors can affect the increase in blood glucose levels including age, hormones, insulin, emotions, psychological state, variety and amount of food consumed and physical activity performed. The purpose of this study was to determine the comparison of increased blood sugar levels before and after 30 minutes of administration of white sugar, palm sugar, and honey to TLM students at STIKes Santa Elisabeth Medan in 2023. The method used was an experiment with a one group pretest-posttest design. Total population of 38 people using total sampling technique. Data analysis using Independent sample T-test. The results of the bivariate analysis showed a p value of 0.000 so it could be concluded that there was a comparison of increased blood sugar levels before and after administration of white sugar, palm sugar, and honey to TLM students at STIKes Santa Elisabet Medan in 2023.